Deficit of glucocorticoid‐induced leucine zipper amplifies angiotensin‐induced cardiomyocyte hypertrophy and diastolic dysfunction. Issue 1 (28th November 2020) - Cappetta, Donato; De Angelis, Antonella; Flamini, Sara; Cozzolino, Anna; Bereshchenko, Oxana; Ronchetti, Simona; Cianflone, Eleonora; Gagliardi, Andrea; Ricci, Erika; Rafaniello, Concetta; Rossi, Francesco; Riccardi, Carlo; et al.
Abstract: Poor prognosis in heart failure and the lack of real breakthrough strategies validate targeting myocardial remodelling and the intracellular signalling involved in this process. So far, there are no effective strategies to counteract hypertrophy, an independent predictor of heart failure progression and death. Glucocorticoid‐induced leucine zipper (GILZ) is involved in inflammatory signalling, but its role in cardiac biology is unknown. Using GILZ‐knockout (KO) mice and an experimental model of hypertrophy and diastolic dysfunction, we addressed the role of GILZ in adverse myocardial remodelling. Infusion of angiotensin II (Ang II) resulted in myocardial dysfunction, inflammation, apoptosis, fibrosis, capillary rarefaction and hypertrophy. Interestingly, GILZ‐KO showed more evident diastolic dysfunction and aggravated hypertrophic response compared with WT after Ang II administration. Both cardiomyocyte and left ventricular hypertrophy were more pronounced in GILZ‐KO mice. On the other hand, Ang II–induced inflammatory and fibrotic phenomena, cell death and reduction in microvascular density, remained invariant between the WT and KO groups. The analysis of regulators of hypertrophic response, GATA4 and FoxP3, demonstrated an up‐regulation in WT mice infused with Ang II; conversely, such an increase did not occur in GILZ‐KO hearts. These data on myocardial response to Ang II in mice lacking GILZ indicate that this protein is a new element that can be mechanistically involved in cardiovascular pathology.